2004
DOI: 10.3354/meps273081
|View full text |Cite
|
Sign up to set email alerts
|

Tropical Archaea: diversity associated with the surface microlayer of corals

Abstract: Recent 16S rDNA studies have focused on detecting uncultivated bacteria associated with Caribbean reef corals in an effort to address the ecological roles of coral-associated microbes. Reports of Archaea associated with fishes and marine invertebrates raised the question of whether Archaea might also be part of the coral-associated microbial community. DNA analysis of mucus from 3 reef-building species of Caribbean corals, Montastraea annularis complex, Diploria strigosa and D. labyrinthiformis in the US Virgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
130
2
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(140 citation statements)
references
References 48 publications
6
130
2
1
Order By: Relevance
“…In this group, clones were found related to coral bacterial symbionts previously found in the Caribbean coral Montastraea faveolata (Sunagawa et al, 2009), Siderastrea siderea (Sekar et al, 2008) and the Mediterranean coral Oculina patagonica . Although Bacteroidetes have been previously detected in healthy corals (Sekar et al, 2008), an increase in Bacteroidetes was associated with Black Band Disease (Cooney et al, 2002;Frias-Lopez et al, 2002, 2004Barneah et al, 2007). Bacteroidetes were also reported to increase in corals exposed to various stress conditions (Vega-Thurber et al, 2009).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In this group, clones were found related to coral bacterial symbionts previously found in the Caribbean coral Montastraea faveolata (Sunagawa et al, 2009), Siderastrea siderea (Sekar et al, 2008) and the Mediterranean coral Oculina patagonica . Although Bacteroidetes have been previously detected in healthy corals (Sekar et al, 2008), an increase in Bacteroidetes was associated with Black Band Disease (Cooney et al, 2002;Frias-Lopez et al, 2002, 2004Barneah et al, 2007). Bacteroidetes were also reported to increase in corals exposed to various stress conditions (Vega-Thurber et al, 2009).…”
Section: Discussionmentioning
confidence: 97%
“…Scleractinian corals, the primary framework builders of coral reefs, comprise a mutualistic interaction between the coral and a dinoflagellate of the genus Symbiodinium, and also contain diverse populations of microorganisms (Bacteria, Archaea, Eucarya and viruses) (Rohwer et al, 2001(Rohwer et al, , 2002Pantos et al, 2003;Kellogg, 2004;Ritchie and Smith, 2004;Bourne and Munn, 2005;Koren and Rosenberg, 2006) that have apparently co-evolved with the corals (Ritchie and Smith, 2004;Rohwer and Kelly, 2004). This has recently led to the idea that the host (coral animal) and its associated microorganisms should be considered as a holobiont (Rohwer et al, 2002;Rosenberg et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative studies have described the associated bacteria, especially the bacteria living in the mucus on the surface of corals (Ducklow and Mitchell 1979), and some concluded the specificity of these communities (Rohwer et al 2001;Bourne and Munn 2005). Archae were also reported to live in association with corals (Kellogg 2004;Wegley et al 2004). One study, based on microscopic investigation, reported the discovery of a symbiotic cyanobacteria with in the coral tissue (Lesser et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Reef-building corals are associated with a dynamic, highly diverse consortium of microorganisms that includes protists, bacteria, archaea and endolithic algae and fungi (Shashar and Stambler, 1992;Bentis et al, 2000;Rohwer et al, 2002;Baker, 2003;Kellogg, 2004;Wegley et al, 2004;Rosenberg et al, 2007;Harel et al, 2008). To study the phylogenetic diversity of the bacterial and archaeal components, sequencing the 16S rRNA gene (16S rDNA) is commonly used because of its ability to identify the species without the need for laboratory cultivation.…”
Section: Introductionmentioning
confidence: 99%